Social work in public health and hospitals - Palmer, Sharon Duca, 1965- (Oakville, Ont. : Apple Academic Press, 2011)
'Social Work in Public Health and Hospitals deals with a variety of issues on social work in hospital settings and public policy issues. Included are articles on hospital stays for the elderly, identifying postnatal depression during well-child visits, breast-feeding and awareness of health recommendations, maternal health services in Nigeria, children living with parents with HIV and AIDS, patients' rights in hospitals, harm reduction in hospitals, and more. In addition to hospitals, the book looks at public health services at rural and community clinics, at university hospitals, and at doctors' offices.'--Publisher's website.
Includes bibliographical references and index.
Keywords: Social work; Public Health Practice; Social Welfare; Community-based social services